Mass housing in Ukraine building typologies and catalogue of series : 1922-2022 - Malaia, Kateryna 1988-; Meuser, Philipp 1969- (DOM publishers, 2024)
Housing is the most omnipresent urban typology. Housing is also the essential architecture of the human condition. Perhaps more than any other architectural species, housing determines how urbanites construct their lives and build their shared futures. The full-scale war of aggression in Ukraine, started by the Russian Federation in 2022, has disproportionally affected housing and residential infrastructure. The destruction is so targeted and the damage so significant that it has disfigured entire neighbourhoods and erased entire cities. With the scale of damage and loss in mind and the future wide-ranging reconstruction that will inevitably occur after the war, this study examines the history and typologies of mass housing in Ukraine. It does so to evaluate what is lost, explain the diversity of modes of urban living in Ukrainian cities, and finally, reconsider the narrative of how Ukrainian housing came about. The study covers the last 100 years: the time of the most dramatic expansion and changes in the character of Ukrainian cities. It begins with the experimental buildings constructed in the Soviet Central and Eastern Ukraine and Polish Western Ukraine in the 1920s and 1930s, continues by looking at type projects from the Stalin era, as well as the serial apartment blocks built during the reigns of Khrushchev and Brezhnev and in the late USSR. Finally, it showcases individually designed yet typical residential buildings from the turbo-capitalist period of the 1990s and 2000s. With the help of archival materials—texts, blueprints, and photographs—and contemporary documentation, the authors analyse 40+ examples of Ukrainian-designed or modified housing types. Through uncovering the Ukrainian context and the work of Ukrainian architects, design institutions, contractors, and developers, the history of Ukrainian housing is emancipated from the Russian narrative of the Soviet past...
Frontispizseite: This title is part of the Histories of Ukrainian Architecture programme initiated by DOM publishers in response to Russia's attack on Ukraine’s sovereignty on 24 February 2022
Keywords: Geschichte 1922-2022; Architektur; Ukraine; Wohnungsbau; Plattenbau; Bildband